Astrobiological implications of dim light phototrophy in deep-sea red clays. (February 2017) - Das, Anindita; Singh, Tanya; LokaBharathi, P.A.; Dhakephalkar, Prashant K.; Mallik, Sweta; Kshirsagar, Pranav R.; Khadge, N.H.; Nath, B. Nagender; Bhattacharya, Satadru; Dagar, Aditya Kumar; Kaur, Prabhjot; Ray, Dwijesh; et al.
Highlights: Aerobic anoxygenic phototrophs (AAP) dominated dark abyssal red clay TVBC-08, that are hydrothermally altered. Purple/green sulphur bacterial enrichments indicate an active S-cycle in CIB red clays. Anaerobic chemolithotrophy followed by anoxygenic phototrophy lead to oxygenic photoautotrophy during hydrothermal cooling. Hydrothermal emissions promote photoautotrophy. These emissions include chemiluminiscence by sulphide nano-clusters. These could be some of the lowest photosynthetic limits on Earth and are astrobiological significant for Mars and beyond. Abstract: Red clays of Central Indian Basin (CIB) under influence of trace of Rodriguez Triple Junction exhibited chemoautotrophy, low temperature hydrothermal alterations and photoautotrophic potential. Seamount flank TVBC-08, hosting such signatures revealed dominance of aerobic anoxygenic phototroph Erythrobacter, with 93% of total 454 pyrosequencing tags. Subsequently, enrichments for both aerobic ( Erythrobacter ) and anaerobic anoxygenic phototrophs (green and purple sulphur bacteria) under red and white LED light illumination, with average irradiance 30.66 W m −2, were attempted for three red-clay sediment cores. Successful enrichments were obtained after incubation for c.a. 120 days at 4°± 2 °C and 25°± 2 °C, representing ambient psychrophilic and low temperature hydrothermal alteration conditions respectively. During hydrothermal cooling, a microbial succession from anaerobic chemolithotrophy to oxygenic photoautotrophy through anaerobic/aerobic anoxygenic phototrophic microbes is indicated. Spectral absorbance patterns of the methanol extracted cell pellets showed peaks corresponding to metal sulphide precipitations, the Soret band of chlorosome absorbance by photosystem II and absence of peaks at Qy transition band. Dendritic nano-structures of metal sulphides are common in these sediments and are comparable with other sulphidic paleo-marine Martian analogues. Significant blue and redshifts have been observed for the experimental samples relative to the un-inoculated medium. These observations indicate the propensity of metal-sulphide deposits contributing to chemiluminiscence supporting the growth of phototrophs at least partially, in the otherwise dark abyss. The effects of other geothermal heat and light sources are also under further consideration. The potential of phototrophic microbial cells to exhibit Doppler shift in absorbance patterns is significant towards understanding planetary microbial habitability. Planetary desiccation could considerably influence Doppler effects and consequently spectral detection techniques exo-planetary microbial life.